Formation pressure evolution and its causes for the reservoirs of the upper Triassic Xujiahe formation in the northeast portion of the Sichuan basin, China. Issue 6 (November 2021) - Zhang, Cunjian; Liu, Jingdong; Jiang, Youlu
Overpressure is one of the most important factors for oil and gas charging in petroliferous basins. Research on overpressure evolution and its formation mechanisms is of great significance for predicting formation pressures in oil and gas reservoirs before drilling. However, research methods addressing overpressure evolution are not without issues. Based on the measured formation pressures and fluid inclusions, the evolution of the formation pressures in the Xujiahe Formation in the northeast part of the Sichuan Basin was investigated by PVT and basin simulations and the causes of overpressure were also analyzed. The results show that overpressure in the continental strata began to develop at the bottom of the Middle Jurassic Shaximiao Formation. The pressure coefficients of the Upper Triassic Xujiahe Formation range from 1.01 to 1.90, and belong to the normal pressure and overpressure regimes. The present-day overpressure of the Xujiahe Formation is mainly caused by hydrocarbon generation and tectonic compression. The tight reservoirs are conducive to the formation and preservation of overpressure. The pressures in the Xujiahe Formation experienced two evolution processes, namely an "increase-decrease-increase" (eastern area) process and an "increase-decrease" (western area) process. Overpressure began to develop in the Middle Jurassic(J2 ) period. Due to the hydrocarbon generation taking place, the formation pressures increased rapidly from the Middle Jurassic(J2 ) period to the early Late Cretaceous (the early part of K2 ) period. The degree of development of overpressure in the western part of the study area was greater than that in the eastern part of the study during the critical charging period (J3 –K1 ). Since the early Late Cretaceous, the formation pressure has gradually decreased due to tectonic uplift and erosion. From the Oligocene (E3 ) period to the present, the formation pressures have increased again in local areas due to tectonic compression.